Mentoring millennials in an Asian context : talent management insights from Singapore - Lim, Paul; Parker, Andrew (Emerald Publishing Limited, 2020)
This book answers an important question: if mentoring research coming out of Western nations have consistently shown that mentoring millennials brings tangible benefits to the organisation in the areas of job satisfaction, organisational commitment and employee retention, would such observations be seen in an Asian context?